Elysium girls - Pentecost, Kate (2020)
When the town of Elysium, Oklahoma, discovers that the world is under the control of two vengeful sister gods--Life and Death--a witch community leader and a trickster join forces to prevent an apocalypse.
When Sal is named Successor to Mother Morevna, a powerful witch and leader of Elysium, she jumps at the chance to prove herself to the town. Though long plagued by false visions of rain, Sal knows she's a leader. Even the arrival of Asa, a human-obsessed demon in disguise, doesn't shake her confidence in her ability-- until a terrible mistake results in both Sal and Asa's exile into the Desert of Dust and Steel. They join a gang of girls headed by Elysium exile and witch Olivia Rosales. Together they create a cavalry of magic powered, scrap metal horses to save Elysium from the coming apocalypse. -- adapted from jacket
Keywords: Goddesses -- Juvenile fiction; Witches -- Juvenile fiction; Good and evil -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy; Goddesses; Good and evil; Magic; Witches; Oklahoma -- Juvenile fiction; Oklahoma; Young adult fiction; Fantasy fiction; Fiction; Juvenile works; Young adult works; Young adult fiction; Fantasy fiction